The Industrial Cluster Plan of the Japanese government and the realities of regional economies in Japan - Kenji Yamamoto (Raumforschung und Raumordnung, 2006)
The purpose of this paper is to introduce a new policy of the Japanese government for the resurgence of regional economies at the beginning of the 21st century and to reexamine its theory and realities. This new policy is the “Industrial Cluster Plan”. The advocators of this plan consider it possible to set up a region artificially. A region cannot, however, be created in such a way, but is a historical construct. Accumulated social capital is important for the recognition of a region. The social capital is decisive for collaborative undertakings among entrepreneurs. This is exemplified by the case of the area along Chuo Freeway, where we can recognize several regions.